Boat navigating Whitehorse Rapids on the Yukon River, Yukon Territory, 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "Whitehorse Rapids copyright 1898 " Same as Hegg 712. Klondike Gold Rush. Additional image in PH Coll 557.12